Digital Politics in Western Democracies : A Comparative Study - Vaccari, Cristian (Book collections on Project MUSE., 2013)
This book presents an analysis of seven advanced Western democracies' digital politics - the US, UK, Australia, Germany, Italy, Spain, and France - from 2006 to 2010. Examining the presentation and consumption of website politics, his study not only refutes claims that the web creates homogenized American-style politics and political interaction but also empirically reveals how a nation's unique constraints and opportunities create unique digital responses. This first large scale, comparative treatment of both the supply and demand sides of digital politics among different national political actors is divided into four parts: research methodology and theoretical challenges; how parties and candidates structure their websites (supply); how citizens use websites to access campaign information (demand); and then ties the research results back into his theoretical framework. Because a key aspect of any political system is how political actors communicate, this book will be invaluable for scholars, students, and practitioners interested in political communication, party competition, party organization, political participation, and the study of contemporary media landscapes writ large.--description provided by publisher.